2016
DOI: 10.1155/2016/7052323
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Functional EST-SSR Markers (Sugarcane) in Cross-Species Transferability, Genetic Diversity among Poaceae Plants, and Bulk Segregation Analysis

Abstract: Expressed sequence tags (ESTs) are important resource for gene discovery, gene expression and its regulation, molecular marker development, and comparative genomics. We procured 10000 ESTs and analyzed 267 EST-SSRs markers through computational approach. The average density was one SSR/10.45 kb or 6.4% frequency, wherein trinucleotide repeats (66.74%) were the most abundant followed by di- (26.10%), tetra- (4.67%), penta- (1.5%), and hexanucleotide (1.2%) repeats. Functional annotations were done and after-eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…Recently, due to the accessibility of a significant amount of genomic information, a lot of EST datasets are available for many crop plants (Savadi et al 2012;Huang et al 2016;Zhu et al 2016). These databases have been successfully utilised to develop novel molecular markers linked to genes of agronomically important traits (Zhang et al 2016;Ul Haq et al 2016). Interestingly, very few EST-SSRs or genelinked markers were developed and tested in P. pinnata (Huang et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, due to the accessibility of a significant amount of genomic information, a lot of EST datasets are available for many crop plants (Savadi et al 2012;Huang et al 2016;Zhu et al 2016). These databases have been successfully utilised to develop novel molecular markers linked to genes of agronomically important traits (Zhang et al 2016;Ul Haq et al 2016). Interestingly, very few EST-SSRs or genelinked markers were developed and tested in P. pinnata (Huang et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Simple sequence repeats (SSRs) are distributed throughout the genome, including coding or genic region of the nuclear genome (Zhu et al 2016;Huang et al 2016). Hence, expressed sequence tags (ESTs) and transcriptome libraries are often used for SSR marker preparation (Huang et al 2016;Ul Haq et al 2016). Moreover, the marker derived from a transcribed portion of genes is involved in variety of metabolic functions and unveils the biological significance (Savadi et al 2012;Zhang et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Their study found a high level of polymorphism (96.3%) among these samples, and cross-transferability of 98.0% and 88.27% within the Saccharum complex and across cereals, respectively. Ul haq et al [30] procured 10,000 ESTs across 20 plants, and used a computational method to evaluate 267 EST-SSRs and synthesize 63 EST-SSRs. Among those, expansion genetics allowed identification of 42 markers amplifying 519 alleles.…”
Section: Cross-species Transferabilitymentioning
confidence: 99%
“…After the advent of PCR, the improvement of different molecular markers such as amplified fragment length polymorphism (AFLP), single-nucleotide polymorphism (SNP), inter simple sequence repeats (ISSRs), simple sequence repeats (SSR), and several new concepts were used. Different markers were used for the determination of the relationships between plant species by many researchers in tomato cultivars (Nawaz et al, 2015), Poaceae plants (Haq et al, 2016), and Citrullus colocynthis (Verma et al, 2017).…”
Section: Introductionmentioning
confidence: 99%